2020
DOI: 10.1111/nyas.14515
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty of runoff sensitivity to climate change in the Amazon River basin

Abstract: We employ the approach of Roderick and Farquhar (2011) to assess the sensitivity of runoff (R) given changes in precipitation (P), potential evapotranspiration (E p), and other properties that change the partitioning of P (n) by estimating coefficients that predict the weight of each variable in the relative change of R. We use this framework using different data sources and products for P, actual evapotranspiration (E), and E p within the Amazon River basin to quantify the uncertainty of the hydrologic respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Climate is the most basic and important factor affecting runoff, directly changing the land‐gas water cycle structure and causing the spatial and temporal distribution of the water resource system configuration change via the redistributed of precipitation and temperature change (Carmona, Renner, Kleidon, & Poveda, 2020). The present study results showed that annual precipitation had insignificant downward trends (Figure 2), but E p showed significant upward trend (Figure 3) in most regions.…”
Section: Discussionmentioning
confidence: 99%
“…Climate is the most basic and important factor affecting runoff, directly changing the land‐gas water cycle structure and causing the spatial and temporal distribution of the water resource system configuration change via the redistributed of precipitation and temperature change (Carmona, Renner, Kleidon, & Poveda, 2020). The present study results showed that annual precipitation had insignificant downward trends (Figure 2), but E p showed significant upward trend (Figure 3) in most regions.…”
Section: Discussionmentioning
confidence: 99%
“…From the IPCC fifth assessment report (IPCC, 2013), the global average surface temperature rose by 0.85 • C during the period of 1880-2012, and the increasing rate from 1951 to 2012 was twice as fast as that since 1880. Human activities such as agricultural irrigation, industrial water use and the construction of reservoirs are already changing the hydrological cycle [8,9]. In the context of global climate, the distribution of water resources has been temporally and spatially altered by the comprehensive effects of human activities to a certain extent [10][11][12].…”
Section: Introductionmentioning
confidence: 99%